2007
DOI: 10.1542/peds.2006-2092
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pain and/or Fever at 3 to 7 Days for Children With Acute Otitis Media Not Treated Initially With Antibiotics: A Meta-analysis of Individual Patient Data

Abstract: The risk of a prolonged course was 2 times higher for children < 2 years of age with bilateral acute otitis media than for children > or = 2 years of age with unilateral acute otitis media. Clinicians can use these features (ie, age of < 2 years and bilateral acute otitis media) to inform parents more explicitly about the expected course of their child's otitis media and to explain which features should prompt parents to contact their clinician for reexamination of the child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 34 publications
0
41
0
3
Order By: Relevance
“…56 Pain associated with AOM can be substantial in the first few days of illness and often persists longer in young children. 57 Antibiotic therapy of AOM does not provide symptomatic relief in the first 24 hours 58-61 and even after 3 to 7 days, there may be persistent pain, fever, or both in 30% of children younger than 2 years. 62 In contrast, analgesics do relieve pain associated with AOM within 24 hours 63 and should be used whether antibiotic therapy is or is not prescribed; they should be continued as long as needed.…”
Section: Treatment Of Otalgiamentioning
confidence: 99%
See 1 more Smart Citation
“…56 Pain associated with AOM can be substantial in the first few days of illness and often persists longer in young children. 57 Antibiotic therapy of AOM does not provide symptomatic relief in the first 24 hours 58-61 and even after 3 to 7 days, there may be persistent pain, fever, or both in 30% of children younger than 2 years. 62 In contrast, analgesics do relieve pain associated with AOM within 24 hours 63 and should be used whether antibiotic therapy is or is not prescribed; they should be continued as long as needed.…”
Section: Treatment Of Otalgiamentioning
confidence: 99%
“…Children younger than 2 years with AOM may take longer to improve clinically than older children, 57 and although they are more likely to benefit from antibiotics, 31,32 AOM in many children will resolve without antibiotics. 62 A clinically significant benefit of immediate antibiotic therapy is observed for bilateral AOM, 62,96 Streptococcus pneumoniae infection, or AOM associated with otorrhea.…”
Section: Initial Antibiotic Therapymentioning
confidence: 99%
“…It has been confirmed that these children benefit more from immediate antibiotic treatment (IA) 37 .…”
Section: Groups At Risk For a Poor Outcome: Immediate Antibiotic Treamentioning
confidence: 96%
“…All the reasons explained above, along with the side effects of antibiotics, support the current watchful waiting approach in response to a diagnosis of AOM, and deferring antibiotic treatment for cases with poor outcomes (those who have not improved in 48-72 hours) [34][35][36][37] (IA). When taking this approach, the physician must be sure that he will be able to follow up with the patient 1,19,25 .…”
Section: Antibiotic Treatment or The Watchful Waiting Approachmentioning
confidence: 99%
See 1 more Smart Citation